Mindshift in autism: a call to professionals in research, clinical, and educational settings - McVey, Alana J.; Jones, Desiree R.; Waisman, T. C.; Raymaker, Dora M.; Nicolaidis, Christina; Maddox, Brenna B. (Frontiers in Psychiatry, 2023)
Autistic people often have poor outcomes over the life course, including in health, education, employment, and community inclusion. Many professionals working with Autistic adults in research, clinical, and educational settings devote their careers to trying to improve such outcomes. However, we maintain that real progress cannot happen without a fundamental mindshift. The status quo for professionals is to view autism as an illness. Instead, the neurodiversity movement encourages us to value and embrace autism as an aspect of human diversity and asks us to view Autistic people as a marginalized group that experiences significant disparities. While some professionals may be adopting language and concepts from the neurodiversity movement, we argue that making this mindshift fundamentally changes our practice across research, clinical, and educational settings. In this perspective, we call on professionals to embrace this mindshift to reduce discrimination and stigma, halt the spread of harmful ideologies, and help Autistic adults live fulfilling lives.